Buddhist Approach To The Psycho-Social Issues Relating To The Families Of Missing Persons In The Civil War In Sri Lanka (FROM 1983 - 2009) - Mudalige, Janaka; Vuḍḍhikaro, Phramahā Somboon; Sedere, Upali M.; Edirisinghe, Daya; Ariyaratne, Iromi; Mudalige, M. J. M. (Advances in Social Sciences Research Journal, 2018)
The title of the Dissertation is “Buddhist Approach to the Psycho-social Issues Relating to the Families of Missing Persons in the Civil War in Sri Lanka (from 1983 _2009)” Researcher attempted weather Buddhist approach could help in minimization or eradication of psychosocial issues of the families of missing persons within the above scope. The loved ones of a missing person due to whatever the reason behind it live in constant severe mental and physical pain with lot of suffering. The complete loss or absence of hope, often waiting for years for good news creates the agony worst. The objective of the research is to find out existing Psycho-Social Issues in a mixture of quantitative & qualitative research, aiming at the recommendations on a global perspective. Research question was finding out what happened to the missing people which has become a top priority in the world while families are living with uncertainty and severe mental agony and objectives of the research were to ascertain the magnitude of the humans suffering due to the loss of their loved one/s. Methodology of the research was framed on the basis of Mix of Qualitative and Quantitative data & information research findings were developed based on the analysis of data and testing of hypothesis. Buddhist approach to the Psycho-social issues were found significantly important in the study. Researcher established the actual gap between the facts and figures based on 18891 total complaints received during the period of the mandate of PCICMP vs the total complaints announced at the discussions of United Nations in Geneva 23586. The importance of expediting the balance complaints and grievances were found. The lessons learnt from the Buddhist approach is well proved in conflict resolution in terms of Justice, Accountability of the Government, the process of Reconciliation, the Compensation, and Establishment of all possible ways & means in order to avoid future occurrences were concluded.